Una profesión en desarrollo: John F. C. Turner en Arequipa - Gyger, Helen (2021)
This article explores the intersection of aided self-help housing and modernist architectural culture through the early career of the English architect John F. C. Turner, who emerged as a prominent theorist of aided self-help housing beginning in the 1960s. The focus is on Turner’s development of an architectural practice following his arrival in Peru in 1957, at the invitation of architect and planner Eduardo Neira. Turner spent the next couple of years in Arequipa, working for a government agency charged with regularizing the city’s urbanizaciones populares. This culminated in a trial aided self-help housing project initiated after an earthquake in 1958 caused widespread damage to Arequipa’s housing stock. The article explores how these seminal on-the-ground experiences informed Turner’s later theoretical writings.